Pengaruh Current Ratio dan Debt to Equity Ratio terhadap Return Saham Pada Perusahaan Subsektor Otomotif dan Komponen yang terdaftar di Bursa Efek Indonesia - Ramadhani, Melda Aulia; Rinaldi, Muhammad; Sudirman, Sitti Rahma; Ramadhani, Muhammad Harits Zidni Khatib (EKALAYA : Jurnal Ekonomi Akuntansi, 2023)
This research aims to empirically examine the effect of the Current Ratio (CR) and Debt to Equity Ratio (DER) on Stock Return. The sample in this study consisted of 11 automotive and component companies listed on the Indonesia Stock Exchange from 2015 to 2019. The sampling technique used is purposive sampling. The data were analyzed using multiple linear regression analysis. The results of this study prove that CR has a positive effect on stock returns, but the debt-to-equity ratio does not affect stock returns. This research implies that companies in mak, ing decisions, can better consider CR. The study is also expected to contribute to assisting investors in investing their valuable assets into the stock market, especially in automotive and component companies. Further research can add more industries, samples, years, and variables for better results. This research aims to empirically examine the effect of the Current Ratio (CR) and Debt to Equity Ratio (DER) on Stock Return. The sample in this study consisted of 11 automotive and component companies listed on the Indonesia Stock Exchange from 2015 to 2019. The sampling technique used is purposive sampling. The data were analyzed using multiple linear regression analysis. The results of this study prove that CR has a positive effect on stock returns, but the debt-to-equity ratio does not affect stock returns. This research implies that companies, in making decisions, can better consider CR. The study is also expected to contribute to assisting investors in investing their valuable assets into the stock market, especially in automotive and component companies. For better results, further research can add more industries, samples, years and variables.